2022
DOI: 10.4103/jomfp.jomfp_337_21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immunohistochemical expression of E-cadherin in pleomorphic adenoma and adenoid cystic carcinoma

Abstract: Background: Pleomorphic adenoma (PA) and adenoid cystic carcinoma (ADCC) are benign and malignant salivary gland tumors, respectively, with distinct behavior. They have similar origins and cell components. E-cadherins are the main homophilic cell adhesion molecules, which play a central role in maintaining epithelial integrity, functioning in intercellular adhesion and differentiation. Hence, changes in E-cadherin function are reflected in the morphologic events associated with the cellular arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although not significant, we observed low E‐cadherin immunostaining in the membrane and cytoplasm in 65% of PA cases, 78% of ACC cases, and 65% of MEC cases. Previous studies investigating the same salivary gland tumors found different E‐cadherin immunostaining, 8–11,13–15 although other authors did not observe any significant difference when PA and ACC were compared as a whole 12 . These findings could be attributable to tumor heterogeneity and loss of cellular cohesion due to extracellular matrix.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Although not significant, we observed low E‐cadherin immunostaining in the membrane and cytoplasm in 65% of PA cases, 78% of ACC cases, and 65% of MEC cases. Previous studies investigating the same salivary gland tumors found different E‐cadherin immunostaining, 8–11,13–15 although other authors did not observe any significant difference when PA and ACC were compared as a whole 12 . These findings could be attributable to tumor heterogeneity and loss of cellular cohesion due to extracellular matrix.…”
Section: Discussionmentioning
confidence: 84%
“…The EMT is a biological event that occurs in many cancers, including those originating in salivary glands. [10][11][12] It involves a polarized epithelial cell that is altered to a mesenchymal phenotype with increased migratory and invasive capacities. 5 The present results demonstrated a significantly higher expression of the transcription factors SNAIL, SLUG, and TWIST in the malignant neoplasms studied than PA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations